Protection of agricultural property in the light of the act on shaping the agricultural system - Litwiniuk, Przemysław (Przegląd Prawa Rolnego, 2019)
The purpose of the deliberations presented in this article is to assess the protection of agricultural property in the light of the Act of 11 April 2003 on shaping the agricultural system, taking into account its amendments of 2016 and 2019. In the author’s opinion, the provisions of this Act that serve the purpose of the protection of agricultural property should be interpreted in the light of the principles derived from Article 23 of the Constitution of the Republic of Poland and from the perspective of the intentions expressed in the preamble to this Act. However, the instruments contained therein serve mainly to regulate trading in agricultural property and to exercise the powers of the state acting with the help of a trustee in the dominium sphere, acquiring the ownership of agricultural land from private entities. It is therefore concluded that the “family holding” defined in the Act does not correspond in its normative form to the constitutional model, and the statutory protection granted to it is only apparent and ineffective.